Data center environment monitoring system - Santos, D.; Mataloto, B.; Ferreira, J. C. (CCIOT 2019: Proceedings of the 2019 4th International Conference on Cloud Computing and Internet of Things, 2019)
The Internet of things (IoT) is applied to many cases in the smart cities topic. We apply an IoT-developed platform using LoRa communication to a Data Center to understand temperature behavior within a concentration of servers and the working behavior of these server machines. We describe our work as an IoT platform to measure temperature, humidity, and energy consumption in these data centers. In the end, the gradient temperature was found in the rack, and the increasing temperature is correlated with energy consumption and the backup routines in the night. Our developed approach can be used to understand CPU usage and related temperature and the energy consumption.